Central Image Archiving and Management System for Multicenter Clinical Studies: Lessons from Low-dose CT for Appendicitis Trial - Yousun Ko; Jin Woo Choi; Dong Hyun Kim; Kyong Joon Lee; Sang Soo Shin; Ji Young Woo; Seong Whi Cho; Bong Soo Kim; Kyoung Ho Lee (대한영상의학회지, 2017)
This special report aimed to document our experiences in implementing the Central Imaging Archiving and Management System (CIAMS) for a multicenter clinical trial, Low-dose CT for Appendicitis Trial (LOCAT), supported by the Korean Society of Radiology and Radiology Imaging Network of Korea for Clinical Research. LOCAT was a randomized controlled trial to determine whether low-dose CT is non-inferior to standard-dose CT with respect to the negative appendectomy rate in patients aged from 15 to 44 years. Site investigators downloaded the CT images from the site picture archiving and communication system servers, and uploaded the anonymized images to the primary server. CIAMS administrators inspected the images routed to the secondary server by a cross-check against image submission worksheets provided by the site investigators. The secondary server was automatically synchronized to the tertiary backup server. Up to June 2016, 2715 patients from 20 sites participated in LOCAT for 30 months. A total of 2539 patients' images (93.5%, 2539/2715) were uploaded to the primary server, 2193 patients' worksheets (80.8%, 2193/2715) were submitted, and 2163 patients' data (79.7%, 2163/2715) were finally monitored. No data error occurred.